Early infant diagnosis of HIV infection at the John F. Kennedy Medical Center, Monrovia, Liberia - I. U, Umar; Adeiza, M. A.; Ideh, R. C.; Ogbuagu, O. (HIV research & clinical practice, 2022)
Background: Vertical transmission accounts for majority of new HIV infections among children worldwide. Ninety percent of HIV-positive children reside in Sub- Saharan Africa with their infection predominantly acquired via vertical transmission. In 2004, the vertical transmission rate of HIV in Africa was estimated at 25 − 40% but, remarkably, the rate has significantly decreased to less than 5% in most African countries following implementation and expansion of prevention of MTCT (PMTCT) programs. Objective: To determine the rate of and factors associated with vertical transmission of HIV among attendees of early infant diagnosis (EID) program of an academic and community-based tertiary facility in Liberia. Design: A retrospective cross-sectional analysis. Methods: A retrospective review of medical records of babies seen at Pediatric Unit of Infectious Disease Clinic of John F Kennedy Medical Center (JFKMC) in Monrovia, Liberia between January 1, 2016 and December 31, 2020. All subjects were children born to HIV-positive mothers and who had HIV DNA PCR testing performed between the ages of 6 weeks and 6 months. Children who suffered early neonatal death and those who did not undergo PCR testing were excluded. Demographics of mother to child pairs as well as factors known to influence vertical transmission of HIV such as partial (15.8%) or full (84.2%) participation in prevention of MTCT (PMTCT) programs, mode of delivery, breastfeeding and utilization of post-exposure prophylaxis were collected and assessed. Binomial logistic regression analyses were used to assess factors associated with vertical transmission. Results: During the study timeframe, 284 children had a HIV DNA PCR test with a male:female ratio − 1.3:1. Sixteen tested positive (conducted at a mean of 155 days post birth) giving a vertical transmission rate of 5.6%. For 239 mothers (84.2%) who had full PMTCT, 1.3% of their children tested positive, while for 45 mothers (15.8%) who had partial PMTCT, 28.8% of their children being positive. Two hundred and seventy six children (97%) had exclusive breastfeeding, 13 of whom tested positive while 2 children who were mixed fed tested positive. Children who had Nevirapine vs no prophylaxis (OR = 1.89[95% CI 1.16 − 2.96]), were delivered via caesarian section vs vaginal delivery (OR= 2.26[95% CI 1.92 − 4.12].) and full versus partial participation in PMTCT programs (OR = 4.02[95% CI 2.06 − 4.13] were more likely to have negative HIV test. Conclusion: Vertical transmission rate was found to be high in Liberia and may be driven by suboptimal PMTCT program participation including post-exposure prophylaxis for infants. Therefore, strategies to scale up and improve uptake of PMTCT services are needed to mitigate the burden of HIV among children.